Analisis Kesuksesan Pemasaran Global pada KFC : Kajian Literasi - Tasya Alivia Putri; Fikri Syahrul Ramadhan; Danendra Amantha Widhia; Mohamad Zein Saleh (Universitas 45 Surabaya, 2024)
Global marketing has become one of the keys to success for international companies, including KFC. This article discusses KFC's success in marketing its products globally, starting from the strategies implemented to the challenges faced. This analysis includes a discussion of global marketing concepts, a brief profile of KFC, and special strategies that have made this brand known throughout the world. The research was conducted using a literature review method to understand how KFC has succeeded in adapting to different markets. It is hoped that this article will provide insight into the importance of global marketing for the success of international business.